Metal detecting as a social formation: A longitudinal survey study from Finland - Visa Immonen; Joonas Kinnunen (United Kingdom, 2025)
The hobby of metal detecting has mostly been examined from the perspectives of archaeology and heritage administration. Although fulfilling archaeological needs, such an approach neglects the social analysis of this pastime. In 2019, we conducted a survey of metal detector enthusiasts and heritage professionals in Finland, the results of which are compared with those of a corresponding survey carried out in 2014. Within five years, metal detecting has become an established practice, and following the Finnish custom, registered associations for amateurs have emerged to organize the field. This longitudinal survey highlights its importance to civil society, with regard to the ways in which metal detecting develops as a hobby and as a means for amateurs to engage with heritage management.